Linking celebrity endorsement and luxury brand purchase intentions through signaling theory: A serial-mediation model involving psychological ownership, brand trust and brand attitude - Sanan Waheed Khan; Umer Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Celebrity endorsements create a magnitude of meaningful differences among luxury brands that subsequently generate skyrocketing sales fueled bycelebrity-inspired consumer's confidence. The present study explores the impact of celebrity endorsements as a modern marketing technique on customers' purchase of luxury brands. Applyingthe signaling theory and quantitative research approach, a standardized questionnaire facilitated a survey of 300 potential buyers of luxury brandsin Pakistan. The partial-least squares structural equation model (PLS-SEM) based findings revealed that celebrity endorser has a favorable impact on consumers' perceptions of psychological ownership, brand trust and brand attitude. Notably, the customer's psychological ownership, brand trust, and brand attitude significantly mediate celebrity endorsement and luxury brand purchase intentions through multiple pathways. The presentstudy offers new insights on the theoretical and practical consequences of celebrity endorsement for luxury brands, especially pinpointing the potential mediating channels (i.e.,psychological ownership, brand trust, and brand attitude) that can significantly enhance customer's confidence and purchase intentions of luxury brands.
Keywords: 330; celebrity endorsement; psychological ownership; brand trust; brand attitude; signaling theory; luxury brand purchase intentions; Pakistan